13 Efficacy on individualized starting dose (ISD) and fixed starting dose (FSD) of niraparib per investigator-assessment (IA) in newly diagnosed advanced ovarian cancer (OC). (13th November 2020) - Graybill, W; Mirza, M; González-Martin, A; O'Malley, D; Gaba, L; Yap, OWS; Guerra, E; Rose, PG; Baurain, J; Ghamande, S; Denys, H; Prendergast, E; et al.
Abstract : Introduction: Niraparib is a poly(ADP-ribose) polymerase inhibitor approved for maintenance treatment of patients with newly diagnosed or recurrent OC that responded to platinum-based chemotherapy and treatment in heavily-pretreated recurrent OC. Here we report efficacy in patients receiving the FSD and ISD in the PRIMA/ENGOT-OV26/GOG-3012 trial (NCT02655016 ). Methods: This double-blind, placebo-controlled, phase 3 study randomized 733 patients to receive niraparib or placebo for 36 months or until disease progression/toxicity. A protocol amendment introduced ISD: 200 mg in patients with body weight <77 kg or platelets <150, 000/µL, or 300 mg in all others. The primary endpoint was PFS by blinded independent central review (BICR). IA PFS was a sensitivity analysis. At the primary analysis data cut, follow-up was 11.2 months and 17.1 months in the ISD and FSD subgroups, respectively. An ad hoc analysis of IA PFS was performed using an updated data cut with additional 6 months follow-up. Results: BICR and IA PFS were highly concordant in the overall population. Efficacy of niraparib based on IA PFS in FSD vs ISD subgroups for each data cut were similar (table 1 ). Dose interruptions, modifications, and hematologic toxicity were lower with the ISD. Exposure–response data supported the clinical data. Conclusions: The 200- or 300-mg ISD by baseline body weight and platelet counts demonstrated comparable efficacy while improving the safety profile of niraparib. Use of this regimen for first-line maintenance of advanced OC patients is approved by the US FDA. Funded by: GlaxoSmithKline NCT: NCT02655016